A grid-based model of backwasting of supraglacial ice cliffs on debris-covered glaciers - Buri, Pascal; id_orcid:0 000-0003-3890-2109; Pellicciotti, Francesca; Steiner, Jakob F.; Miles, Evan S.; Immerzeel, Walter W. (International Glaciological Society, 2016)
Ice cliffs might be partly responsible for the high mass losses of debris-covered glaciers in the Hindu Kush-Karakoram-Himalaya region. The few existing models of cliff backwasting are point-scale models applied at few locations or assume cliffs to be planes with constant slope and aspect, a major simplification given the complex surfaces of most cliffs. We develop the first grid-based model of cliff backwasting for two cliffs on debris-covered Lirung Glacier, Nepal. The model includes an improved representation of shortwave and longwave radiation, and their interplay with the glacier topography. Shortwave radiation varies considerably across the two cliffs, mostly due to direct radiation. Diffuse radiation is the major shortwave component, as the direct component is strongly reduced by the cliffs’ aspect and slope through self-shading. Incoming longwave radiation is higher than the total incoming shortwave flux, due to radiation emitted by the surrounding terrain, which is 25% of the incoming flux. Melt is highly variable in space, suggesting that simple models provide inaccurate estimates of total melt volumes. Although only representing 0.09% of the glacier tongue area, the total melt at the two cliffs over the measurement period is 2313 and 8282 m3, 1.23% of the total melt simulated by a glacio-hydrological model for the glacier’s tongue. ISSN:0260-3055 ISSN:1727-5644